Prevalence and Risk Factors for Malnutrition in Patients With Parkinson's Disease - Yang, Tianting; Zhan, Zhen; Zhang, Liang; Zhu, Jun; Liu, Yi; Zhang, Lili; Ge, Jianchao; Zhao, Ying; Zhang, Li; Dong, Jingde (Frontiers in Neurology, 2020)
Objectives: This study aimed to investigate the relationship between nutritional status and Parkinson's disease (PD) features. Methods: The cohort was composed of 556 Parkinson's patients who were admitted to the hospital. Patients were categorized as normal nutrition or at risk of malnutrition/already malnourished. Questionnaires, physical examinations, and biochemical tests were conducted. The relationship between nutrition status and PD was analyzed using t-tests, x2 tests, and logistic regression models. Results: The prevalence of malnutrition (defined as a Mini Nutritional Assessment (MNA) score < 17) was 39.2%, and 30.3% of patients were at risk of malnutrition (17 ≤ MNA score ≤ 23.5). There was no difference in gender and age between the different nutrition groups (P<0.05). Patients at risk of malnutrition and those who were malnourished had a longer course of disease, more severe motor symptoms, a higher stage of PD according to the Hoehn and Yahr (H-Y) classification, a lower body mass index (BMI) index, a lower cognitive score, higher levels of depression and anxiety, and more serious nonmotor symptoms (P<0.05) than patients with normal nutrition. There were differences in adenosine deaminase, albumin, phosphorus, chlorine, total protein and uric acid between the two groups (P<0.05). High Unified PD Rating Scale (UPDRS-III) scores, high H-Y stages, and dyskinesia were risk factors for malnutrition in PD patients, while high levels of total protein, uric acid and chlorine were protective factors that led to good nutrition (P<0.05). Conclusions: Our results showed that dyskinesia, disease severity, total protein levels, uric acid levels and chlorine levels were associated with nutritional status among Chinese PD patients. The findings of this study indicate the significance of the early detection and prevention of malnutrition to improve the quality of life of PD patients.